On Revenue Recycling and the Welfare Effects of Second-Best Congestion Pricing in a Monocentric City - Ioannis Tikoudis; Erik T. Verhoef; Jos N. van Ommeren (Tinbergen Institute, 2013)
This paper explores the interactions between congestion pricing and a tax-distorted labor market within a monocentric urban equilibrium model. We compute the efficiency gains of various second-best policies, i.e. combinations of toll schemes and revenue recycling programs, with a predetermined level of public revenue. We find that 35% of the space-varying road tax does not reflect marginal external congestion costs, but rather functions as a Ramsey-Mirrlees tax, i.e. an efficiency enhancing mechanism allowing space differentiation of the labor tax. Such a space-varying tax adds a quite different motivation to road pricing, since it can produce large welfare gains even in the absence of congestion. We show that both a cordon toll and a flat kilometer tax achieve over 80% of these gains when combined with specific types of revenue recycling, such as labor tax cuts or public transport subsidies. Sensitivity analysis shows that the optimal type of revenue recycling depends on the level of inefficiency in the provision of public transport prior to the introduction of congestion pricing.
Keywords: R41; R48; H23; H76; J20; R13; R14; 330; Second-best road pricing; revenue recycling; monocentric city